Віддзеркалення теми революції 1956 р. в Угорщині у Закарпатських газетах того часу - Вароді Наталія; Váradi Natália; Natalia Varadi (Київський політехнічний інститут імені Ігоря Сікорського, 2021)
Резюме. В статті розглядається проблематика подій революції 1956 р. в Угорщині крізь призму преси того часу. Простежується, що радянська влада висвітлювала угорські події як контрреволюційні, спрямовані проти влади та народу. Встановлено, що в радянській пресі на Закарпатті було приділено велику увагу Угорщині часів революції. Влада ставила за мету створити таку картину, що все те, що відбувається в Угорщині, є несправедливим, шкідливим та противладним. Доповіді про події в Угорщині були зосереджені на страті угорських комуністів, вбивствах радянських солдатів та захопленні партійних і державних установ.

Abstract. Numerous papers have been written about the history of the Hungarian Revolution of 1956 both in Hungary and beyond its borders in the past decades. The archival documents of Ukraine and the former Soviet Union are under research too. Numerous data prove that the actions aiming to crush the War of Independence were directly governed from Transcarpathia. Archival data also confirm the reminiscence of the Transcarpathian Hungarian witnesses, according to which the Soviet military and political centre was set up in Uzhgorod, from where the defeat of the Hungarian Revolution was directed. The reminiscence of the Soviet soldiers reveals that the first military corps crossed the border with the purpose of crushing the revolution on October 24. Since travelling became impossible due to the strictly closed borders after the Second World War, people living in the Soviet Union could not keep in touch with Hungary. The postal connections were severely controlled. The Soviet authorities permitted the inhabitants to order only a couple of foreign publications, in few copies. Even the Hungarian Communist Party-press could be ordered and read only by few people. The majority of the population was informed about the local and foreign world and events mainly by the Soviet press, which was the mouthpiece of the Communist Party of the Soviet Union. Getting a relatively realistic picture about the outside world was only possible through foreign radio broadcasting. The Hungarian people mainly listened to Kossuth Radio, but some people could reach western broadcasts and listened to the Free Europe Radio, for instance. These sources of news were available during the revolution too. After the revolution was suppressed, the Transcarpathian newspapers celebrated the «victory over the counter-revolution» and judged its participants (the «horthysts», the «fascists» — as they called them). Only rejective writings were published; articles with the slightest sign of sympathy could be published neither in the central nor in the local papers. The importance of the press is confirmed by everyday experience, numerous studies and scientific reports. Its public opinion-forming power is particularly significant. Analysis of the press is necessary to understand the conditions of an age. To understand the essence of the 1956 Revolution, it is crucial and vital to study the contemporary press. The events of the 1956 Revolution in Hungary received a great response in the local papers. Even after 64 years, the articles that appeared in the Transcarpathian newspapers during the ‘56 Revolution are extremely telling. It is obvious how the Soviet authorities wanted to influence the opinion of Transcarpathian inhabitants about the Revolution. From October 25, in the papers, the following questions arise almost every day: what caused, triggered the revolution, what actually happened in October? In local press sometimes 3–4 articles deal with the Revolutionary actions from the Soviet point of view. This article is press study research on the 1956 Revolution.
The Echo of the 1956 Hungarian Revolution in the Contemporary Transcarpathian Printed Press
Keywords: газета; аналіз статей; революція 1956 р.; пропаганда; комуністичний лідер